Nilai Ketuhanan dan Nilai Moral Kebangsaan sebagai Landasan Etika Sosial dalam Menjaga Kerukunan - Puji Lestari, Endah; Saputra, Anan; Puji Rahayu (JPT : Jurnal Pendidikan Tematik, 2025)
Divinity and national moral values ​​are crucial in building the character and morals of the Indonesian people. These values ​​serve as a foundation for a safe and peaceful society. Therefore, a sound spiritual and moral foundation is necessary for effective implementation of values ​​such as integrity and wisdom. This research employs a descriptive approach, while its nature is qualitative. The purpose of this paper is to understand the relationship between divinity and moral values, their relationship, and how they are applied in everyday life. Furthermore, the results, along with several previous studies, demonstrate that these values ​​significantly influence the smooth development of the character of students, citizens, and society.